Historical review of Argentine activities in geomagnetism and aeronomy - Schneider, Otto (1994)
Research in the disciplines embraced under the general concept of Geomagnetism and Aeronomy belongs in Argentina, with very few exceptions, to the XXth Century. Changes in the administrative and academic organization of such work have frequently occurred all over the world, partly as a consequence of the explosive development of techniques and theories, and partly in the framework of the ever changing historical scenarios within the participating nations. This also applies to the case of Argentina, still a young country. With the exception of a very few outstanding leaders, organizers and teachers we must, alas, refrain from quoting the numerous individual scientists and technicians who have contributed to this development; it is impossible to do justice to all of them, but many names will appear in the references. Suffice it in the present context to remark that they were recruited, in addition to geophysicists proper, among physicists, geologists, geodesists, mathematicians, astronomers, engineers, and members of the armed forces.